Experience-Based Tourism Marketing: Understanding Tourist Experiential Value in Sanur, Bali - Wirawan, Putu; Ni Wayan Mega Sari Apri Yani; Ni Luh Gde Sari Dewi Astuti (Brilliant International Journal Of Management And Tourism, 2026)
This study examines experience-based tourism marketing by understanding how experiential value is constructed among tourists in Sanur, Bali, as a mature coastal destination with strong cultural characteristics. The research addresses the problem that tourism marketing practices are still predominantly promotion-oriented and have not fully captured the holistic experience of tourists as a core value in destination marketing. Therefore, the objective of this study is to explore how experiential value is formed through the interaction between tourists and key destination elements. This research employs a qualitative interpretative approach, utilizing observation, in-depth interviews, and documentation involving tourists, tourism stakeholders, and local communities. Data were analyzed using thematic interpretative analysis to identify patterns and dimensions of tourist experiences. The findings reveal that experiential value is constructed through the interaction of four main elements: servicescape, local culture, social interaction, and marketing practices. Servicescape and local culture were found to be the most dominant factors influencing tourists’ positive experiences, while social interactions and informal marketing practices strengthened emotional attachment and destination perception. The study proposes a conceptual model expressed as EV = f(SC, BL, IS, PM), indicating that experiential value is a function of these interconnected elements. The results emphasize that tourism marketing should shift from promotion-based approaches to experience-oriented strategies. This study contributes theoretically by expanding the experiential marketing framework in tourism and practically by providing strategic insights for destination stakeholders to enhance competitiveness through holistic experience management.